1992
DOI: 10.1093/infdis/166.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Epitopes of Herpes Simplex Virus Type 1 Glycoprotein B that Bind Type-Common Neutralizing Antibodies Elicit Type-Specific Antibody-Dependent Cellular Cytotoxicity

Abstract: A panel of 45 well-characterized monoclonal antibodies (MAbs) reactive to glycoprotein B (gB) of herpes simplex virus (HSV) type 1 was tested by ELISA and in antiviral functional assays (that included virus neutralization, antibody-dependent cellular cytotoxicity (ADCC), and antibody-dependent complement-mediated lysis), using type 1 or 2 virus strains. All MAbs were ELISA-reactive. Eleven of the MAbs mediated neutralization and 9 mediated ADCC. All of the ADCC epitopes were contained within the amino-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In addition, we demonstrated here that the expression of the gB-Y889A mutant on the surfaces of infected cells was significantly higher than that of the gB-LL871-872AA and gB-T887A mutants. It is well established that gB on the cell surface is a potent inducer of the immune response in vivo (5,6,40,41). In fact, it has been demonstrated that lysis of HSV-1-infected cells by natural killer cells, which play critical roles in the initial defense against herpesvirus infection in the central nervous system (29), is correlated with cell surface expression of gB (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we demonstrated here that the expression of the gB-Y889A mutant on the surfaces of infected cells was significantly higher than that of the gB-LL871-872AA and gB-T887A mutants. It is well established that gB on the cell surface is a potent inducer of the immune response in vivo (5,6,40,41). In fact, it has been demonstrated that lysis of HSV-1-infected cells by natural killer cells, which play critical roles in the initial defense against herpesvirus infection in the central nervous system (29), is correlated with cell surface expression of gB (5).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the biological significance of cell surface expression of HSV-1 glycoproteins remains unclear at present, although several reports have implied a potential role(s) for herpesvirus envelope glycoproteins on the cell surface (9, 28). However, expression of HSV-1 envelope glycoproteins on the surfaces of infected cells is considered to mark those cells for the host immune response, because HSV-1 glycoproteins on the cell surface are potent inducers of the immune response (5,6,40,41). In particular, it has been reported that lysis of HSV-1-infected cells by natural killer cells correlates with expression of gB on the cell surface (5).…”
mentioning
confidence: 99%
“…Furthermore, the effect of the gB-T887D mutation, which was predicted to mimic the phosphorylation of Thr-887, was different from that of T887A in gB, and the phenotype of the gB-T887D virus was identical to that of wild-type virus. It has been reported that gB on the cell surface is a potent inducer of the immune response in vivo (4,5,49,50), and it has been speculated that the downregulation of the cell surface expression of gB by endocytosis could involve immune evasion (7). In fact, the lysis of HSV-1-infected cells by natural killer cells correlates with the cell surface expression of gB (4).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, gB is essential for attachment and entry of the virus into host cells, fusion, and cell-to-cell spread (42, 53), and its role in viral egress has been suggested (40). In vivo, HSV-1 gB is a potent inducer of the immune response (4,20,43,47,49,50) and has also been involved in neuroinvasion (18,34,51,62).HSV-1 gB is a 904-amino-acid (aa) type I membrane glycoprotein composed of a 696-aa ectodomain, a 69-aa transmembrane domain, and a 109-aa carboxy-terminal domain. The cytoplasmic domain of gB is the longest among HSV-1 glycoproteins, which suggests that it might play a role during infection.…”
mentioning
confidence: 99%
“…In vitro, gB is essential for attachment and entry of the virus into host cells, fusion, and cell-to-cell spread (42,53), and its role in viral egress has been suggested (40). In vivo, HSV-1 gB is a potent inducer of the immune response (4,20,43,47,49,50) and has also been involved in neuroinvasion (18,34,51,62).…”
mentioning
confidence: 99%